Quantum biology to enhance CO2 fixation - Coughlan, J.L. (2021)
β-methylmalyl-CoA lyase (MCL) is a bacterial metabolic enzyme with activity in acetyl-CoA assimilation pathways. Bifunctional MCL is found in the ethylmalonyl pathway where it reversibly converts (S)-malyl-CoA into acetyl-CoA and glyoxylate and combines propionyl-CoA with glyoxylate into β-methylmalyl-CoA. Interestingly, MCL has demonstrated activity with (S)-citramalyl-CoA in vitro, a reaction attributed to distantly related citrate lyase. Despite having different tertiary structures and diverged amino acid sequences, the participating residues of the active site of this family of enzymes are well conserved. The non-reversible mechanism of citrate lyase has been characterised both experimentally and computationally, but there is still much to learn about the mechanism of MCL, to address key questions such as how the reversible reaction is able to proceed. Two crystal structures of MCL from R.sphaeroids are available. In this work, molecular dynamics (MD) simulations have been performed on one of these structures with a single active site occupied by propionyl-CoA and glyoxylate. No reliable parameters were available for glyoxylate in the CHARMM forcefield, thus, they have been optimised following the protocol set out for CGenFF. Molecular docking has been used to predict the conformations of the bonded substrates, followed by MD simulations to assess the stability of these complexes. To better describe the active site, the enzyme was then modelled using hybrid quantum mechanics/molecular mechanics (QM/MM) methods. This will facilitate the prediction of the intermediate states adopted over the course of the reaction.